New record of the Oriental house rat, Rattus tanezumi, in Nepal inferred from mitochondrial Cytochrome B gene sequences. Issue 1 (2nd January 2018) - Adhikari, Pradeep; Han, Sang-Hyun; Kim, Yoo-Kyung; Kim, Tae-Wook; Thapa, Tej Bahadur; Subedi, Naresh; Kunwar, Amar; Banjade, Maniram; Oh, Hong-Shik
Abstract: This study determines the presence of R . tanezumi from in Nepal using morphological and molecular analyses. Morphologically, it is indistinguishable with R. rattus owing to similar fur colour and morphometric data. However, molecular identification and phylogenetic analysis using sequences of the mitochondrial DNA (mtDNA) Cytochrome B ( CytB ) gene revealed two different species R . rattus and R . tanezumi from collected specimens. The genetic distance between R . rattus and R . tanezumi was found 0.043. In phylogenetic tree, the clade of R . tanezumi is distinguished into two sub-clades, R . tanezumi found in Nepal, and East Asian countries, China, Laos, Thailand, Viet Nam, and South Korea have genetic distance 0.031, suggesting the different lineages of R . tanezumi . This study confirmed the R . tanezumi present in Nepal. Our findings suggest that morphological analysis and molecular study should be carried out simultaneously for accurate identification of small sized cryptic mammals like R . tanezumi and R . rattus .